2021
DOI: 10.1016/j.compbiomed.2021.104249
|View full text |Cite
|
Sign up to set email alerts
|

Discovering symptom patterns of COVID-19 patients using association rule mining

Abstract: Background The COVID-19 pandemic is a significant public health crisis that is hitting hard on people's health, well-being, and freedom of movement, and affecting the global economy. Scientists worldwide are competing to develop therapeutics and vaccines; currently, three drugs and two vaccine candidates have been given emergency authorization use. However, there are still questions of efficacy with regard to specific subgroups of patients and the vaccine's scalability to the general public. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 86 publications
1
59
0
3
Order By: Relevance
“…Data mining algorithms have only been used to discover symptom patterns in COVID-19 patients [ 52 ] as well as to make predictions about COVID-19 patient severity [ 2 , [7] , [8] , [9] ] and recovery [ 53 ]. The MLP algorithm classified the severe patients with a precision (96.5%), similar to XGBoost [ 9 ] and other multipurpose algorithms [ 7 ], but with the advantage of using laboratory tests.…”
Section: Discussionmentioning
confidence: 99%
“…Data mining algorithms have only been used to discover symptom patterns in COVID-19 patients [ 52 ] as well as to make predictions about COVID-19 patient severity [ 2 , [7] , [8] , [9] ] and recovery [ 53 ]. The MLP algorithm classified the severe patients with a precision (96.5%), similar to XGBoost [ 9 ] and other multipurpose algorithms [ 7 ], but with the advantage of using laboratory tests.…”
Section: Discussionmentioning
confidence: 99%
“…Zoabi and colleagues also developed a model for predicting COVID-19 using machine learning that included fever and cough as the most important symptoms [ 51 ]. Similarly, Tandan and colleagues found that fever, cough, pneumonia, and sore throat were the most frequent features using a rule-based machine learning technique called association rule mining [ 52 ]. Other authors have reported lipid dysregulations in COVID-19 patients, as found in this study, such as that of glycerophospholipid metabolism [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Association rule mining is a well-known data mining approach for determining disease and symptom co-relationships [ 18 – 24 ]. Numerous applications of association rule mining in the healthcare area include forecasting disease based on a patient’s symptoms, determining an adequate treatment for diseases, detecting medication response, and improving medical fraud detection via data mining [ 19 , 25 – 29 ]. Association rule mining generates IF-THEN rules that medical professionals quickly understand.…”
Section: Introductionmentioning
confidence: 99%